Ceftazidime-avibactam versus meropenem in nosocomial pneumonia, including ventilator-associated pneumonia (REPROVE): a randomised, double-blind, phase 3 non-inferiority trial. Issue 3 (March 2018) - Torres, Antoni; Zhong, Nanshan; Pachl, Jan; Timsit, Jean-François; Kollef, Marin; Chen, Zhangjing; Song, Jie; Taylor, Dianna; Laud, Peter J; Stone, Gregory G; Chow, Joseph W
Summary: Background: Nosocomial pneumonia is commonly associated with antimicrobial-resistant Gram-negative pathogens. We aimed to assess the efficacy and safety of ceftazidime-avibactam in patients with nosocomial pneumonia, including ventilator-associated pneumonia, compared with meropenem in a multinational, phase 3, double-blind, non-inferiority trial (REPROVE). Methods: Adults with nosocomial pneumonia (including ventilator-associated pneumonia), enrolled at 136 centres in 23 countries, were randomly assigned (1:1) to 2000 mg ceftazidime and 500 mg avibactam (by 2 h intravenous infusion every 8 h) or 1000 mg meropenem (by 30-min intravenous infusion every 8 h) for 7–14 days; regimens were adjusted for renal function. Computer-generated randomisation codes were stratified by infection type and geographical region with a block size of four. Participants and investigators were masked to treatment assignment. The primary endpoint was clinical cure at the test-of-cure visit (21–25 days after randomisation). Non-inferiority was concluded if the lower limit of the two-sided 95% CI for the treatment difference was greater than −12·5% in the coprimary clinically modified intention-to-treat and clinically evaluable populations. This trial is registered with ClinicalTrials.gov (NCT01808092 ) and EudraCT (2012-004006-96). Findings: Between April 13, 2013, and Dec 11, 2015, 879 patients were randomly assigned. 808 patients were included in the safety population, 726 were included in the clinically modified intention-to-treat population, and 527 were included in the clinically evaluable population. Predominant Gram-negative baseline pathogens in the microbiologically modified intention-to-treat population (n=355) were Klebsiella pneumoniae (37%) and Pseudomonas aeruginosa (30%); 28% were ceftazidime-non-susceptible. In the clinically modified intention-to-treat population, 245 (68·8%) of 356 patients in the ceftazidime-avibactam group were clinically cured, compared with 270 (73·0%) of 370 patients in the meropenem group (difference −4·2% [95% CI −10·8 to 2·5]). In the clinically evaluable population, 199 (77·4%) of 257 participants were clinically cured in the ceftazidime-avibactam group, compared with 211 (78·1%) of 270 in the meropenem group (difference −0·7% [95% CI −7·9 to 6·4]). Adverse events occurred in 302 (75%) of 405 patients in the ceftazidime-avibactam group versus 299 (74%) of 403 in the meropenem group (safety population), and were mostly mild or moderate in intensity and unrelated to study treatment. Serious adverse events occurred in 75 (19%) patients in the ceftazidime-avibactam group and 54 (13%) patients in the meropenem group. Four serious adverse events (all in the ceftazidime-avibactam group) were judged to be treatment related. Interpretation: Ceftazidime-avibactam was non-inferior to meropenem in the treatment of nosocomial pneumonia. These results support a role for ceftazidime-avibactam as a potential alternative to carbapenems in patients with nosocomial pneumonia (including ventilator-associated pneumonia) caused by Gram-negative pathogens. Funding: AstraZeneca.